Financial Development in Sub-Saharan Africa : Promoting Inclusive and Sustainable Growth - Mlachila, Montfort (Departmental Papers; Departmental Paper ;, 2016)
This paper discusses how sub-Saharan Africa's financial sector developed in the past few decades, compared with other regions. Sub-Saharan African countries have made substantial progress in financial development over the past decade, but there is still considerable scope for further development, especially compared with other regions. Indeed, until a decade or so ago, the level of financial development in a large number of sub-Saharan African countries had actually regressed relative to the early 1980s. With the exception of the region's middle-income countries, both financial market depth and institutional development are lower than in other developing regions. The region has led the world in innovative financial services based on mobile telephony, but there remains scope to increase financial inclusion further. The development of mobile telephone-based systems has helped to incorporate a large share of the population into the financial system, especially in East Africa. Pan-African banks have been a driver for homegrown financial development, but they also bring a number of challenges.